STUDENTS’ PERCEPTIONS OF THE USE OF ZOOM AND WHATSAPP IN ELT AMIDST COVID19 PANDEMIC - Suadi Suadi (STAIN Sultan Abdurrahman Kepulauan Riau, 2021)
During the Covid19 pandemic, online learning platforms are solutions to sustain the English Language Teaching (ELT). It is an appropriate platforms option for lecturers to deliver the course materials amidst the covid19 outbreak. Some of the most frequently used platforms are Zoom and WhatsApp. The purpose of this study is to describe the EFL university students’ perceptions of the use of Zoom and WhatsApp in ELT. A virtual class in form of Zoom and WhatsApp was created to enable students to remotely attend the class and at the same time to keep in line with the covid19 health protocol. This study involved 53 students as respondents. The data were obtained through online-based questionnaire and were analyzed based on a mixed method approach by combining quantitative and qualitative method. The result revealed that the virtual class of ELT for EFL University students in form of Zoom and WhatsApp was considered positive by the learners. Although the availability and slow speed internet connection were being problems to use them in ELT, they were also rated effective and efficient in terms of time, place and expense. Moreover, learners agreed that those two online platforms can help them to improve language skills and to reduce shyness in virtual class interaction.